MAKNA KONOTATIF DALAM LIRIK-LIRIK LAGU POPULER KARYA BAND THE SCRIPT (Analisis Semantik) - LAHAMA, MERRY (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT Â This research is entitled â€œConnotative Meaning in Popular Song Lyrics by The Script Band (A Semantic Analysis)â€. The aims of the research are to identify the connotative meaning in the song lyrics, to classify the types of connotative and to analyze the connotative meaning in popular song lyrics by The Script band. This research uses descriptive method. In collecting data, the writer focused on identifying the words and phrases that contain connotative meaning and classify them based on theory of J. N. Hook (in Widarso 1989) which divides the connotative meaning into positive connotative, negative connotative, and neutral connotative. Then the writer uses theory of Geoffrey Leech (1981) to analyze the connotative meaning in popular song lyrics by The Script band. The result of this research showed that there are positive connotative and negative connotative in the song lyrics and there are 25 words and 15 phrases containing the connotative meaning and the connotative meaning have variation in their description. Â Keywords: Connotative, Types of Connotative, Song Lyrics by The Script